Reverse Leakage Current Characteristics of GaN/InGaN Multiple Quantum-Wells Blue and Green Light-Emitting Diodes - Ting Zhi; Tao Tao; Bin Liu; Zili Xie; Peng Chen; Rong Zhang (IEEE Photonics Journal)
The mechanisms of reverse leakage in InGaN/GaN multiple-quantum-wells (MQWs) blue and green light-emitting diodes (LEDs) were studied through analyzing the current–voltage (I–V) characteristics with the temperature ranging from 50 to 350 K. When the reverse bias V is below 12 V, the leakage current is dominated by the variable-range hopping conduction $(T\rm{ < 250\,K)}$ and Poole–Frenkel emission $(T\rm{ > 250\,K)}$ , respectively. As the reverse bias increases $(\vert V\vert \rm{ > 12\,V)}$ , the space-charge-limited conduction mechanism is responsible for the leakage current. It is found that the leakage current is highly associated with the defects density, as well as the trapping capacity of deep level centers; therefore, the lower leakage current of blue LED is mainly attributed to higher thermal activation energy $E_{a}$ due to less deep level centers within GaN/InGaN MQWs structures.